IMPLEMENTATION OF THE AT-TARTIL METHOD IN IMPROVING THE ABILITY TO READ THE QUR'AN AT THE BAITUL AMANAH TPQ - Avanda Salwa Salsabila; Nurdyansyah (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
The ability to read the Qur'an is a fundamental competency that every student in a Qur'anic Education Center (TPQ) should possess to understand and practice Islamic teachings. However, many students still encounter difficulties in reading the Qur'an fluently, pronouncing the letters accurately (makhraj), and applying the rules of tajwid correctly. This condition highlights the need for an effective learning method, one of which is the At-Tartil Method. This study aims to describe the implementation of the At-Tartil Method in improving students' Qur'an reading ability at TPQ Baitul Amanah, explain the assessment system applied, and identify the supporting and inhibiting factors affecting its implementation. This research employed a qualitative approach using a case study design. The research participants consisted of the TPQ principal, teachers, and students. Data were collected through observation, interviews, and documentation, while data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that the At-Tartil Method is implemented systematically through read-and-listen activities, drill exercises, habituation in reading the Qur'an according to makhraj, tajwid, and gharib principles, as well as continuous evaluation. The implementation of this method has been shown to improve students' fluency, accuracy, and reading proficiency. Its successful implementation is supported by the competence of teachers, support from the TPQ principal and parents, and students' learning motivation. Meanwhile, the main obstacles include limited facilities and infrastructure, the absence of placement tests for new students, and inconsistent student attendance and learning discipline. Therefore, the At-Tartil Method can serve as an effective alternative for improving the quality of Qur'an reading instruction in Qur'anic Education Centers.